Понятійний складник концепту «радість» у німецькій та англійській мовах - Дорменєв, Віктор Стефанович; Dormeniev, V. S. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Стаття є спробою розглянути понятійний складник концепту «радість» у німецькій та англійській мовах на матеріалі субстантивно оформленої лексики, що зумовлено категоріальним статусом цього класу. У центрі уваги – німецька лексема Freude й англійська лексема joy як основні номінанти досліджуваної емоції, а також домінанти відповідних синонімічних рядів. Проаналізовано дефініційну та ілюстративну частини різних типів словників, адже словникові статті вважають культурологічно релевантним матеріалом для вивчення концептів, зокрема концептів емоційних. The article is an attempt to consider the notional component of the concept «joy» in German and English on the material of substantively specified vocabulary, that is stipulated by the categorial status of this class. The German lexeme Freude and English lexeme joy are in the focus of attention as the main nominees of investigated emotion and the dominants of corresponding synonymous rows. Definitional and illustrative parts of different types of dictionaries are analyzed, because dictionary entries are considered culturologically relevant material for the study of concepts. The dictionary entry contains not only information of all linguistic levels – phonological, lexical and semantic, phraseological, grammatical. It is also a source of both linguistic data and information of culturological type. As the result of the analysis of the vocabulary, that is the core of the concept, related to the close periphery, common and distinctive features of the semantic and cognitive nominees of emotion of joy in the studied languages are distinguished.
The Notional Component of the Concept «Joy» in German and English
Keywords: концепт; concept; понятійний складник; notional component; номінанти емоцій; nominees of emotions